All‐Polymer Bulk‐Heterojunction Organic Electrochemical Transistors with Balanced Ionic and Electronic Transport. Issue 42 (13th September 2022) - Wu, Xihu; Tam, Teck Lip Dexter; Chen, Shuai; Salim, Teddy; Zhao, Xiaoming; Zhou, Zhongliang; Lin, Ming; Xu, Jianwei; Loo, Yueh‐Lin; Leong, Wei Lin
Abstract: The rapid development of organic electrochemical transistor (OECTs)‐based circuits brings new opportunities for next‐generation integrated bioelectronics. The all‐polymer bulk‐heterojunction (BHJ) offers an attractive, inexpensive alternative to achieve efficient ambipolar OECTs, and building blocks of logic circuits constructed from them, but have not been investigated to date. Here, the first all‐polymer BHJ‐based OECTs are reported, consisting of a blend of new p‐type ladder conjugated polymer and a state‐of‐the‐art n‐type ladder polymer. The whole ladder‐type polymer BHJ also proves that side chains are not necessary for good ion transport. Instead, the polymer nanostructures play a critical role in the ion penetration and transportation and thus in the device performance. It also provides a facile strategy and simplifies the fabrication process, forgoing the need to pattern multiple active layers. In addition, the development of complementary metal–oxide–semiconductor (CMOS)‐like OECTs allows the pursuit of advanced functional logic circuitry, including inverters and NAND gates, as well as for amplifying electrophysiology signals. This work opens a new approach to the design of new materials for OECTs and will contribute to the development of organic heterojunctions for ambipolar OECTs toward high‐performing logic circuits. Abstract : An all‐polymer bulk‐heterojunction (BHJ) organic electrochemical transistor (OECT) with good ambipolar property is achieved through the blending of a new p‐type ladder polymer and a state‐of‐the‐art n‐type ladder polymer. The concept of the BHJ provides a facile strategy to develop ambipolar OECTs with balanced electron and hole transport, and ultimately to achieve high amplification and easy scaling for integrated circuits.